P62 Managing the cardiovascular complications of late syphilis. (23rd May 2012) - Sacks, R; Tipple, C; Goldmeier, D
Abstract : Background: BASHH recommends full clinical examination and chest radiography (CXR) for patients with late syphilis. Steroid cover and cardiology referral are advised for cardiovascular involvement. Recent literature suggests variation in the clinical management of suspected cardiovascular syphilis. Aim: To explore variations in the management of late syphilis in UK GUM clinics and to compare this with current BASHH guidelines. Method: Lead clinicians of UK GUM clinics were invited to complete an electronic survey between November and December 2010 to establish management of late syphilis in their centre. Data collected using the online Survey Monkey system were analysed with Microsoft Excel and SPSS V.18. Results: In total, 34% (53/156) of clinicians approached responded fully or partially to the survey (93% were consultants). An average of nine cases (n=45, SD 10.8) of late syphilis (KC60 codes A4, A5, A6) per clinic were seen between November 2009 and November 2010. Of these, 76% (n=42, range 0–100%) were estimated to have had a full clinical examination (and the use of CXR is described in abstract P62 table 1 ). *Other includes: older patients; HIV+ve patients; those with higher RPR; clinician dependent An ECG or ECHO was ordered routinely, or if the patient has symptoms or signs of cardiovascular syphilis, in 90% and 76% respectively. Cardiology referral was routinely made by 58% (18/31) and 35% (9/26) always used steroids, when managing cardiovascular syphilis. Discussion: Management of late syphilis varies both between clinics and compared with BASHH guidelines. Not all patients are examined or offered a CXR, and in cases with suspected cardiovascular involvement, cardiology referral and use of steroids are variable. Conversely, many patients are over-investigated in the GUM clinic.